2018
DOI: 10.1016/j.tibs.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Embrace of a Mutator: APOBEC Selection of Nucleic Acid Ligands

Abstract: The 11-member APOBEC (apolipoprotein B mRNA editing catalytic polypeptide-like) family of zinc-dependent cytidine deaminases bind to RNA and single-stranded DNA (ssDNA) and, in specific contexts, modify select (deoxy)cytidines to (deoxy)uridines. In this review, we describe advances made through high-resolution co-crystal structures of APOBECs bound to mono- or oligonucleotides that reveal potential substrate-specific binding sites at the active site and non-sequence-specific nucleic acid binding sites distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 137 publications
(257 reference statements)
2
63
0
Order By: Relevance
“…The whole DNA is in a straight‐line binding groove, similar to that predicted by Chen, et al . Compared to other A3‐DNA complexes (Figure S6), the CCC binding mode of 3′‐end of DNA in A3G‐PrA complex is also included in A3A‐DNA and A3G‐CTD2*‐DNA complexes, while the TCC binding mode of 3′‐end of DNA in A3G‐PrB complex is almost identical to those observed in chimeric A3B‐DNA complex and in rA3G‐CD1 in complex with DNA . In contrast, the position of DNA in A3F‐DNA complex is much far away from the catalytic center, different from those in A3G‐PrA, A3G‐PrB, A3A‐DNA and A3B‐DNA complexes.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…The whole DNA is in a straight‐line binding groove, similar to that predicted by Chen, et al . Compared to other A3‐DNA complexes (Figure S6), the CCC binding mode of 3′‐end of DNA in A3G‐PrA complex is also included in A3A‐DNA and A3G‐CTD2*‐DNA complexes, while the TCC binding mode of 3′‐end of DNA in A3G‐PrB complex is almost identical to those observed in chimeric A3B‐DNA complex and in rA3G‐CD1 in complex with DNA . In contrast, the position of DNA in A3F‐DNA complex is much far away from the catalytic center, different from those in A3G‐PrA, A3G‐PrB, A3A‐DNA and A3B‐DNA complexes.…”
Section: Figuresupporting
confidence: 91%
“…The whole DNA is in ak inked-line binding groove, similar to the one predicted by Holden, et al [29] The TCC orientation was observed in A3G-PrBc omplex, locating between A3G-CD2l oop 3a nd a3h elix or loop 5. The whole DNA is in a straight-line binding groove, similart ot hat predicted by Chen, et al [23,43] Compared to other A3-DNA complexes ( Figure S6), [44] the CCC binding mode of 3'-end of DNA in A3G-PrA complex is also included in A3A-DNA and A3G-CTD2*-DNA com-plexes, [34,35] while the TCC binding mode of 3'-end of DNA in A3G-PrBc omplex is almost identicalt ot hose observed in chimeric A3B-DNAc omplex [35] and in rA3G-CD1 in complex with DNA. [27] In contrast, the positiono fD NA in A3F-DNA complex is much far away from the catalytic center, [36] different from those in A3G-PrA,A 3G-PrB, A3A-DNA andA 3B-DNAc omplexes.…”
supporting
confidence: 83%
“…Among the processes involved is RNA and DNA editing mediated by endogenous deaminases. Two different deaminase families are present in mammalian species: the ADARs target double stranded RNA (dsRNA) for deamination of Adenines into Inosines (A-to-I) (3,4), and the APOBECs deaminate Cytosines into Uracils (C-to-U) on singlestranded nucleic acids (ssDNA and ssRNA) (5,6). ADARs interfere with viral infections directly 10 -through hypermutation of viral RNA-and indirectly, through modulation of the intracellular response (7)(8)(9)(10)(11)(12).…”
Section: Main Textmentioning
confidence: 99%
“…The hallmark activity of the APOBEC family of enzymes is catalyzing a zinc ion‐mediated hydrolytic deamination of 2'‐deoxycytidine to 2'‐deoxyuridine in single‐stranded (ss)DNA [reviewed by Refs. ]. In addition to AID and APOBEC1, human cells have the potential to express up to seven different APOBEC3 (A3) enzymes (A3A‐D, A3F‐H).…”
Section: Introductionmentioning
confidence: 99%